Understanding cognitive development : approaches from mind and brain - Landau, Barbara, editor (London : Taylor & Francis, 2013)
The papers in this volume examine the state of the art in key areas of developmental cognitive neuroscience, focusing on theoretically driven research on cognition and its development. The past decade has seen an increasing number of empirical papers on the relationship between brain and cognitive development. But despite the clearly burgeoning interest in this topic, there is a relative paucity of work motivated by deep theoretical questions about the nature of cognition and its development. Many papers are still in the mode of reporting brain-cognition correlations with a focus on regional activations during brain imaging - a useful approach, but one that is limited with respect to its contributions to understanding the structure of cognition and its development. The papers in this special issue of Cognitive Neuropsychology consider a number of domains and mechanisms in cognition, including language, number, space, faces, reading, memory, and attention, and represent the wealth of approaches and techniques that can be used to shed light on the nature of cognitive development in brain and mind. These include cross-species comparisons, studies of development under experiential deprivation or genetic differences, classical developmental experimentation, and imaging techniques such as NIRS and fMRI which have recently been applied to developmental questions. The combination of solid theorizing together with a broad range of approaches allows a critical but constructive look at the latest findings in the field relevant to answering enduring questions about cognition, its development, and its realization in the developing brain.